The Effect of Budget Planning, Budget Implementation, Procurement of Goods and Services, Competence of Human Resources and Budget Politics on Budget Absorption (Empirical Study on Opd Pelalawan District) - Sofia Gusmartina; Nur Azlina; Julita Julita (AFEBI Accounting Review, 2021)
AbstractThis study aims to prove and test the factors that influence budget absorption. The factors tested in this study are budget planning, budget execution, procurement of goods and services, human resource competence and budget politics. The data source used in this research is primary data and data collection is done directly using a questionnaire which is measured using a Likert scale. The population of this study were employees of all offices and regional apparatus organizations in Pelalawan Regency, totaling 27 OPDs. The total sample of this study was 108 respondents with the sampling technique, namely purposive sampling, who were in accordance with the position of the head of the department, the financial technical executive officer and the expenditure treasurer.